Health-Related Quality of Life in Adolescents with Thalassemia - Nonglak Boonchooduang (2018)
© 2015 Informa Healthcare USA, Inc. Children and adolescents with thalassemia suffer from chronicity of the disease and its treatment, including transfusion dependence and complications of iron overload. This study aimed to assess the health-related quality of life of adolescents with thalassemia compared with healthy controls. Sixty-four adolescents with thalassemia aged 13 to18 years and their parents were enrolled in this cross-sectional study, as well as their age- and gender-matched those of the healthy controls (64 participants and their parents). The Pediatric Quality of Life Inventory 4.0 Scales (PedsQL 4.0) self-report form was administered to the adolescents in both groups. Parents were also asked to complete the PedsQL 4.0, parent proxy-report form. The self-reported total, psychosocial, and school functioning scores of the thalassemia patients were significantly lower than those of the healthy controls (p = 0.03, 0.04, and < 0.001, respectively). The parent-reported psychosocial and school functioning scores of the thalassemia group were also significantly lower than those of the controls (p = 0.03 and 0.003, respectively). Among adolescents with thalassemia, the serum ferritin level and comorbidity were the only variables associated with quality of life scores. This study showed that thalassemia negatively affected quality of life. For a better quality of life, thalassemia patients should be monitored for serum ferritin levels and treated for comorbidity as part of their comprehensive health care.